A critical review on advances in TiO2-based photocatalytic systems for CO2 reduction. (5th November 2022) - Domínguez-Espíndola, Ruth Belinda; Arias, Dulce Maria; Rodríguez-González, Claramaria; Sebastian, P.J.
Highlights: CO2 reactivity increases with an increase in the CO2 :H2 O ratio. Acidic solutions rather than pure water are preferable for formic acid formation. High temperatures promote the rate of thermally activated steps such as desorption. Heating promotes high activity for the CO2 hydrogenation reaction. Monolithic photoreactor allows selective production of CO and H2 . Abstract: The growing world population and uncontrolled industrial growth have resulted in elevated energy consumption and harsh emission of toxic agents tearing down the ecosystem. The transformation of a greenhouse gas like CO2 into energy sources, i.e., CO, CH3 OH, CH4, etc. is a promising strategy to alleviate the interlinked issues of environmental pollution, global warming and climate change. This article presents an overview of the fundamentals of photocatalytic systems and the latest developments in CO2 chemical reduction towards solar fuels over titanium dioxide (TiO2 ). The basic principle of photocatalysis states new photocatalyst synthesis and how the current materials can be used to improve the existing catalysts, focusing on the surface area, electrical conductivity, and chemical stability of TiO2 . In the study of the state of the art it was observed that at a lower CH4 /CO2 ratio, more H2 was produced, while a higher feed ratio promoted CO production. The maximum production rate reported for CH4 was 0.64 mmol g -1 h −1, for CO was 158 mmol/h/gcat, and 102 mmol h -1 Kgcat _1 . Detailed insights for enhanced performance, especially factors affecting mass transfer, thermodynamics, selectivity, and reaction mechanism are provided and discussed. This review summarizes and analyzes research work on the photoreduction of CO2 in the presence of TiO2 over the past ten years. State of the art in photocatalytic CO2 chemical reduction over TiO2 emphasizes material design and reactor configurations. One section is dedicated to reactor design optimization and studying the synergic effect in photocatalysis. Also, brief perspectives and the main challenges in photocatalytic CO2 reduction are outlined, which are vital for improving the conversion efficiency of CO2 . The use of solar energy to drive CO2 photocatalytic reactions and the recent progress in this area are also explored and discussed.